Teaching English for Elementary School Students through Communicative Language Teaching - Intan Istiantika; Jade Jatuporn; Anjar Setiawan (International Journal of Research in Education, 2023)
The aim of the implementation Communicative Language Teaching (CLT) in learning process is to change the teacher-centered learning process into student-centered learning, where students have the freedom to move and discuss all available materials. The method is given to students in grades three to six at SDN Jambangan during the Kampus Mengajar program. The CLT method is divided into four, namely the Communicative English teaching method, the practice question method, the question and Answer Session method, the guessing game method. Further, when learning is carried out, it was designed to make communicative activities such as games so that students don't feel bored. This learning process can provide opportunities for students to improve their language skills by using communicative English teaching methods. The findings showed that it is very helpful for educators to provide what is the right method to help students in dealing with existing problems and make learning fun. The students were active during the teaching and learning process. They did the teacher’s instruction cooperatively. Therefore, it can be concluded that learning can be carried out well and feels light when using the right stages. This research also helps the researcher to gain new experiences, which are very valuable experiences for life.